Management of ectopic eruption of bilateral mandibular first permanent molars: a case report and literature review - Zhang, Dandan; Shi, Qiongling; Fang, Linxian; Jiang, Wenxiang; Han, Jie; Wu, Zhifang (Journal of the Pakistan Medical Association, 2023)
Ectopic eruption of the first permanent molars is a local eruption disturbance. The frequency of ectopically erupted first permanent molars is predominant in boys and primarily affects the maxilla. Interceptive treatment for irreversible ectopic eruptions should be initiated early to prevent space loss and the impaction of the second premolars. Herein, we report the case of a six-year-old girl with irreversible ectopic eruption of the bilateral mandibular first permanent molars treated with a modified lingual arch. The mandibular first permanent molars were successfully distalised after six months of treatment, and one year of follow-up showed a satisfactory outcome. The modified lingual arch satisfies not only the clinical aspects of treatment but also the patient’s well-being. However, the lingual arch may disturb tooth eruption in the mixed-dentition stage. Key words: Ectopic eruption; Mandibular first permanent molar; Modified lingual arch.